How will human epidermal growth factor receptor 2-neu data impact clinical management of gastric cancer? - Lorenzen, Sylvie; Lordick, Florian (Current opinion in oncology, 2011)
Purpose of review - Human epidermal growth factor receptor 2 (HER2) amplification and overexpression play a central role in initiation, progression and metastasis of some common cancers, including breast and gastric cancer. About 20% of gastric and esophagogastric junction (EGJ) tumors overexpress HER2, providing a rationale to investigate trastuzumab, a monoclonal antibody directed against HER2, in this setting. This review focuses on the current role of HER2 inhibition as a new treatment option for gastric and EGJ cancer and discusses the optimization of gastric cancer-specific HER2 testing and analysis. - Recent findings - In the phase III ToGA trial, the addition of trastuzumab to chemotherapy significantly improved overall survival without compromising safety in patients with HER2-positive metastatic gastric or EGJ cancer. This improvement was mainly the result of the survival advantage conferred to patients with high expression of the HER2 protein, defined as immunohistochemistry (IHC) 3+ or IHC 2+/fluorescent in-situ hybridization (FISH) +. - Summary - On the basis of the results of the ToGA trial, HER2 status should now be included in the diagnostic workup of patients presenting with advanced gastric and EGJ cancer. The addition of trastuzumab to chemotherapy is a new standard treatment for patients with locally advanced and irresectable, recurrent or metastatic HER2-positive disease.